Cost of borrowing shocks and fiscal adjustment - Oliver de Groot; Fédéric Holm-Hadulla; Nadine Leiner-Killinger (European Central Bank (ECB), 2012)
Do capital markets impose fiscal discipline on governments? We investigate the responses of fiscal variables to a change in the interest rate paid by governments on their debt in a panel of 14 European countries over four decades. This is done in the context of a panel vector autoregressive (PVAR) model, using sign restrictions via the penalty function method of Mountford and Uhlig (2009) to identify structural cost of borrowing shocks. Our baseline estimation shows that a one percentage point rise in the cost of borrowing leads to a cumulative improvement of the primary balance-to-GDP ratio of approximately 1.9 percentage points over 10 years, with the fiscal response becoming significantly evident only two years after the shock. We also find that the bulk of fiscal adjustment takes place via a rise in government revenue rather than a cut in primary expenditure. The size of the total fiscal adjustment, however, is insufficient to avoid the gross government debt-to-GDP ratio from rising as a consequence of the shock. Sub-dividing our sample, we also find that for countries participating in Economic and Monetary Union (EMU) the primary balance response to a cost of borrowing shock was stronger in the period after 1992 (the year in which the Maastricht Treaty was signed) than prior to 1992.
Keywords: C33; E43; E62; H60; 330; Fiscal Policy; long-term interest rates; sign restrictions; vector-autoregressive models